Modeling Patient Journeys for Demand Segments in Chronic Care, With an Illustration to Type 2 Diabetes - Elkhuizen, Sylvia G.; Vissers, Jan M. H.; Mahdavi, Mahdi; van de Klundert, Joris J. (Frontiers in Public Health, 2020)
Chronic care is an important area for cost-effective and efficient health service delivery. Matching demand and services for chronic care is not easy as patients may have different needs in different stages of the disease. More insight is needed into the patient journey to do justice to actual services, experiences of patients and outcomes in each stage. With patient journey we refer to the ‘journey’ of the patient along the services received within a demand segment of chronic care. We developed a generic framework for describing patient journeys and provider networks to relate demand, services, resources, costs and outcomes. We developed also a generic operational model for modelling patient journeys for different demand segments. We applied this approach to T2D patients. Diabetes care is a form of chronic care for patients suffering diabetes mellitus. We studied the performance of T2D networks, using a descriptive model template with as components: demand, services, structure, behaviour, outcomes. For identifying and describing demand we made use of the following demand segments within the diabetes type 2 population: patients targeted for prevention, patients with stage 1 diabetes treated by GP by lifestyle advice, patients with diabetes stage 2 treated by GP with also oral medication, patients with stage 3 diabetes treated by GP with also insulin injections, patients with stage 4 diabetes with complications treated by internal medicine specialists. We used a model to describe the flows between the different health states. The model allowed us to follow the patient journey through the health care system of a cohort of newly diagnosed diabetes patients, and to make a projection of the resource requirements of the different demand segments over the years. In the paper we elaborate the methodology developed for relating demand, services, structure, behaviour and outcomes for a specific patient group, and focus on the role of demand segments. We illustrate our approach with an example of a T2D care network in a case study in The Netherlands. Finally we reflect on the role of demand segmentation in analysing and improving the diabetes care delivery process.